Book Review: Burghouwt, G. (ed.) Airline Network Development in Europe and its Implications for Airport Planning - Neufville, Richard de (European Journal of Transport and Infrastructure Research, 2008)
This book is a remarkable achievement. Dr. Burghouwt deserves our congratulations and thanks for producing this text, especially so early in his career. The standard he has set promises well for future contributions the profession may expect from him. The text is clearly the current benchmark for analysis and description of air transport networks. Every researcher in the area ought to be familiar with it. Whether you agree with his approach and interpretations or not, it constitutes a ‘must-read’ reference. The text is full of interesting analyses that others may want to emulate. It offers a most interesting discussion of the recent historic evolution (from 1990 to 2003) of airline networks in Europe as they worked their way through the first decade of airline deregulation and intra-European “open skies”.